2011
DOI: 10.4103/0970-1591.91435
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless circumcision - An Indian experience

Abstract: Context:Traditionally, circumcision wounds are closed by absorbable sutures. However, certain alternative methods are also being utilized to overcome the shortcomings of the conventionally used method for circumcision wound closuring. In the current study, the use of tissue glue ((iso amyl 2-cyanoacrylate) has been compared with traditional suturing for the approximation of circumcision wounds. In our study, both the methods were found to be comparable with significantly less time consumed in glue group.Aims:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Some studies have reported that wound approximation using tissue glue was associated with a shorter operation time, a lower rate of wound infection, and less postoperative pain than wound approximation using sutures [7,9,14]. The reported rate of postoperative bleeding after wound approximation using tissue glue is 2.2-6.7%, which is comparable to the reported rate of postoperative bleeding after wound approximation using sutures [7][8][9][10]15].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Some studies have reported that wound approximation using tissue glue was associated with a shorter operation time, a lower rate of wound infection, and less postoperative pain than wound approximation using sutures [7,9,14]. The reported rate of postoperative bleeding after wound approximation using tissue glue is 2.2-6.7%, which is comparable to the reported rate of postoperative bleeding after wound approximation using sutures [7][8][9][10]15].…”
Section: Discussionsupporting
confidence: 78%
“…Most studies of sutureless circumcision using tissue glue have reported superior cosmetic results compared with standard wound closure using interrupted sutures [7][8][9][10]. Some studies have reported that wound approximation using tissue glue was associated with a shorter operation time, a lower rate of wound infection, and less postoperative pain than wound approximation using sutures [7,9,14].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[16] However, tissue adhesive closure in general surgery has a somewhat higher wound dehiscence rate compared with sutures. [17] Tiwari et al [18] showed a wound disruption rate of 6.8% (3/44) in boys and men (mean age 31 years) using tissue adhesive, while other case series including both men and boys found a very low rate of wound disruption. [14] However, these case series were small and follow-up rates were not clearly stated.…”
Section: Discussionmentioning
confidence: 99%